2016
DOI: 10.1089/crpc.2015.29011.prg
|View full text |Cite
|
Sign up to set email alerts
|

“The Immune Conundrum”: Acquired Hemophilia A, Immune Thrombocytopenia, and Neutropenia in a Patient with Pancreatic Cancer

Abstract: Background: Malignancy-associated bleeding can pose diagnostic dilemmas. We report a unique case of paraneoplastic acquired hemophilia A (AHA), immune thrombocytopenia (ITP), and immune neutropenia in a patient with pancreatic adenocarcinoma.Case Presentation: A 66-year-old male with newly diagnosed pancreatic cancer and normal preoperative hematological evaluation was taken to the operating room for pancreaticoduodenectomy. The operation was aborted due to empyema of the gall bladder, cholangitis, and local e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Usually AHA is seen in post operative period as seen in literature review by S. Reitter et al in 4 cases of pancreatic cancer [ 4 ]. Similarly Mavroeidis et al reported AHA in postoperative case carcinoma of ampulla of vater after two month of surgery which was attributed to peritoneal metastatic disease which was also confirmed by Geethakumari et al adenocarcinoma of pancreas [ 10 , 11 ]. None of the cases reported in preoperative period as per our knowledge.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Usually AHA is seen in post operative period as seen in literature review by S. Reitter et al in 4 cases of pancreatic cancer [ 4 ]. Similarly Mavroeidis et al reported AHA in postoperative case carcinoma of ampulla of vater after two month of surgery which was attributed to peritoneal metastatic disease which was also confirmed by Geethakumari et al adenocarcinoma of pancreas [ 10 , 11 ]. None of the cases reported in preoperative period as per our knowledge.…”
Section: Discussionmentioning
confidence: 77%
“…Mavroeidis et al and Geethakumari et al had reported paraneoplastic hemophilia associated with pancreatic cancer [ 10 , 11 ]. We report our experience of another case of paraneoplastic hemophilia associated with periampullary cancer in an elderly patient in preoperative period after thorough investigation and management.…”
Section: Discussionmentioning
confidence: 99%
“…In certain cases, AHA may develop following major surgery, including pancreatoduodenectomy ( 11 , 12 , 15 ). APCC ( 16 ) and recombinant activated factor VII (NovoSeven ® ) ( 17 ) preparations are typically used in the acute phase of AHA for hemostasis ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as these hemophilic patients age, not only hepatic malignancies but also bile duct cancers and pancreatic cancers are developing and requiring surgery if possible 11 . Although some case reports have been published in the abdominal surgical area, no systematic reports have been found in the updated literature 12‐15 …”
Section: Discussionmentioning
confidence: 99%
“…11 Although some case reports have been published in the abdominal surgical area, no systematic reports have been found in the updated literature. [12][13][14][15] The group of one of the authors reported the results of hepatectomy in hemophilia patients in 2018. 16 The study reported on 10 patients and showed no differences in operative time, blood loss, red blood cell transfusion rate, major complication rate, and mortality rate.…”
Section: Discussionmentioning
confidence: 99%